Species composition and feeding guilds of birds utilizing palm oil mill effluent (POME) area in Carey Island, Malaysia - Hassan-Aboushiba, A.B.; Ramli, R.; Sofian-Azirun, Mohd (2011)
A study was conducted in Carey Island, Peninsular Malaysia to determine species composition and feeding guilds of birds that utilized Palm Oil Mill Effluent (POME) ponds. The presence of birds in the area was recorded by a direct observation technique (using binoculars and video camera) from January to December 2009. A total of 31 species of birds which can be classified into 11 families were recorded. Egrets and herons are the most abundant birds, while other waterbirds such as sandpipers, snipes, lapwings, and grebe are presence only in a small number either occasionally or throughout the year. In term of feeding guild, most birds belong to Piscivore/Insectivore (57.14%) and only few species are Insectivore (4.76%). Presence of many bird species with variety of feeding guilds indicated that POME ponds are indeed providing an attractive habitat or foraging site for birds.